A Randomized Trial of Azithromycin Versus Amoxicillin for the Treatment of Chlamydia trachomatis in pregnancy - Jennifer Kacmar; Emily Cheh; Andrea Montagno; Jeffrey F. Peipert (Hindawi Limited, 2001)
Objective: To compare the compliance, side effects and efficacy of amoxicillin and azithromycin for the treatment of Chlamydia trachomatis infection in pregnancy.